The Effect of Debt to Equity Ratio on Earnings Management With Good Corporate Governance As The Moderating Variable - Maharani, Shinta; Prastiwi, Arum (Journal of International Conference Proceedings, 2023)
This study aims to empirically prove the effect of Debt to Equity Ratio on Earnings Management with the moderating variable of Good Corporte Governance represented by the composition of the board commisioners and the board commissioner meeting frequencies. This study employs a quantitative approach utilizing secondary data of the financial report and annual reports as the main data source. The population in this study include financial companies listed on the Indonesian Stock Exchange (IDX) between 2019 and 2021, from which the 77 samples were selected through purposive sampling, the data are analyzed by multiple regression processed by SPSS software. The results of this study exhibit that high Debt to Equity RatioÂ Â is likely to result in high earnings management. Good Corporate Governance represented by Composition of Board Commissioners does not dwindle the effect of Debt to Equity Ratio on Earnings Management while Good Corporate Governance represented by Board Commissioner meeting frequencies reduce the effect of Debt to Equity Ratio on Earnings management.